A computer-aided method for digital controller design via optimization - Nagar S.K.; Pal J.; Sharma J.D. (My University, 2025)
A computational algorithm for the design of digital controllers is presented in this paper. The design procedure adopted here is based on matching the frequency response of open-loop system with a reference model. The controller parameters are obtained by formulating the design problem as unconstrained optimization problem. The performance of the proposed method is illustrated by two examples. © 1990.